2008
DOI: 10.1016/j.bandl.2007.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Task related modulation of the motor system during language processing

Abstract: Recent neurophysiological and brain imaging studies have shown that the motor system is involved in language processing. However, it is an open question whether this involvement is a necessary requisite to understand language or rather a side effect of distinct cognitive processes underlying it. In order to clarify this issue we carried out three behavioral experiments, using a go-no go paradigm. Italian verbs expressing hand actions, foot actions or an abstract content served as stimuli. Participants used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
148
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(169 citation statements)
references
References 42 publications
17
148
2
2
Order By: Relevance
“…These studies, among many others (e.g., Sato et al, 2008;Mirabella et al, 2012;Aravena et al, 2012Aravena et al, , 2014, suggest that verb-induced motor activation is not a rigid, inflexible affair, but is instead sensitive to attentional and situational factors that we are only beginning to understand. It is essential to realize, however, that the mere fact that there is some variability regarding when and how the motor features of verb meanings are retrieved does not imply that those features are not really long-term components of the concepts or that they are not really subserved by the precentral motor cortices.…”
Section: Processing Dynamicsmentioning
confidence: 99%
“…These studies, among many others (e.g., Sato et al, 2008;Mirabella et al, 2012;Aravena et al, 2012Aravena et al, , 2014, suggest that verb-induced motor activation is not a rigid, inflexible affair, but is instead sensitive to attentional and situational factors that we are only beginning to understand. It is essential to realize, however, that the mere fact that there is some variability regarding when and how the motor features of verb meanings are retrieved does not imply that those features are not really long-term components of the concepts or that they are not really subserved by the precentral motor cortices.…”
Section: Processing Dynamicsmentioning
confidence: 99%
“…For instance, Hauk, Johnsrude, and Pulvermuller (2004) found overlap in premotor cortex between movement of foot and fingers and during reading of foot-or hand-related action verbs (e.g., "kick", "pick"). Likewise, areas in premotor cortex activated during observation of actions done with different effectors are also activated on reading of sentences describing these actions (AzizZadeh, Wilson, Rizzolatti, & Iacoboni, 2006; see also Raposo, Moss, Stamatakis, & Tyler, 2009;Boulenger, Hauk, & Pulvermuller, 2009;Tettamanti et al, 2005; but see Postle, McMahon, Ashton, Meredith, & de Zubicaray, 2008;Sato, Mengarelli, Riggio, Gallese, & Buccino, 2008). From these and other findings, it has been concluded that understanding action language involves activating parts of premotor cortex in a somatotopic way, as is also observed during motor control (e.g., Woolsey, 1963).…”
Section: Introductionmentioning
confidence: 79%
“…One of these issues is the need to determine whether language-induced motor activations are exclusively lexical or are dependent to some extent on the semantic context. One possibility is that the activation of the motor cortex occurs automatically about 150-200 ms after the onset of action verbs, as part of their lexical processing (Pulvermüller et al, 2005;Boulenger et al, 2006;Buccino et al, 2001;Nazir et al, 2008;Sato et al, 2008). Another alternative is that the activation of the motor cortex associated with reading is a non-automatic, context-dependent process, involving lexical-semantic integration across the sentence.…”
Section: Introductionmentioning
confidence: 99%